DIGITALISASI PENCATATAN KEUANGAN DAN LAPORAN KEUANGAN PADA UMKM KOPI 76 DENGAN MICROSOFT EXCEL - Nainggolan, Yohanna Thresia; Farisa, Anis; Muti'ah, Hamnah Al; Isnaeni, Rabiatul; Setiawan, Marta (Jurnal Pengabdian Masyarakat Khatulistiwa, 2025)
ABSTRACTThis community service activity is based on the problems of Kopi 76 MSMEs in manual financial recording that is not structured enough and difficulty in preparing financial reports, thus hampering performance evaluation, strategic decision making, and access to funding. The purpose of the activity is to improve the competence of MSME actors in digitizing transaction recording and preparing financial reports based on accounting standards using Microsoft Excel. The implementation method involves a participatory approach through three stages: preparation (observation and pre-test), implementation (socialization, transaction data input practice, interactive simulation, and technical assistance), and evaluation (post-test and analysis of practical skills). The results of the activity showed a significant increase in partner understanding, the ability to record digital transactions with increased account classification accuracy, and efficiency in preparing basic financial reports in 2 hours. This training succeeded in encouraging transparency in financial management, operational optimization, and the potential for expanding access to funding through accurate data. The success of this participatory training model is recommended for replication in other MSMEs with adjustments to specific needs.Keywords: MSME, Financial Report, Microsoft Excel, Training, Coffee ShopABSTRAKKegiatan pengabdian ini didasari oleh permasalahan UMKM Kopi 76 dalam pencatatan keuangan manual yang kurang terstruktur dan kesulitan menyusun laporan keuangan, sehingga menghambat evaluasi kinerja, pengambilan keputusan strategis, serta akses pendanaan. Tujuan kegiatan adalah meningkatkan kompetensi pelaku UMKM dalam mendigitalisasi pencatatan transaksi dan penyusunan laporan keuangan berbasis standar akuntansi menggunakan Microsoft Excel. Metode pelaksanaan melibatkan pendekatan partisipatif melalui tiga tahap: persiapan (observasi dan pre-test), pelaksanaan (sosialisasi, praktik input data transaksi, simulasi interaktif, dan pendampingan teknis), serta evaluasi (post-test dan analisis kemampuan praktis). Hasil kegiatan menunjukkan peningkatan signifikan pemahaman mitra, kemampuan mencatat transaksi digital dengan akurasi klasifikasi akun meningkat, serta efisiensi waktu penyusunan laporan keuangan dasar dalam 2 jam. Pelatihan ini berhasil mendorong transparansi manajemen keuangan, optimalisasi operasional, dan potensi perluasan akses pendanaan melalui data akurat. Keberhasilan model pelatihan partisipatif ini direkomendasikan untuk direplikasi pada UMKM lain dengan penyesuaian kebutuhan spesifik.Kata Kunci:  UMKM, Laporan Keuangan, Microsoft Excel,  Pelatihan, Kedai Kopi